Purchase Price Review in the Infrastructure Industry - Mir, Aized H.; Abidi, Sohail; Durrani, Amer Z. (World Bank, Washington, DC, 2014)
The Pakistan Infrastructure Implementation Capacity Assessment (PIICA) analysis of the cost of materials, construction inputs, and technical services across the region can help in better understanding of the various dimensions of the infrastructure construction industry. Such a study can also help in analyzing common perceptions regarding the existing disparity in cost of doing business, reasons for migration of technical, skilled, and unskilled personnel to regional countries: quality of construction; and other similar issues. The purpose of this analysis is to assess the relative differences in: (i) professional salary structures; (ii) cost of construction inputs across regional countries; and (iii) contractors working (unit) rates. The effectively decreasing charge rates and salary levels over the past decade accentuates the growing trend among professionals towards seeking more lucrative jobs in the overseas market. Pakistan not only has the highest cost of inputs in the region but when compared to the United Arab Emirates (UAE) which has the lowest input costs in the region, material input costs are 400 percent higher in Pakistan. When adverse effects of other variables like old, inefficient equipment, systematic weaknesses and inefficiencies, corruption, and transparency issues are also considered, the rates despite seeming to be "competitive" may well, in fact, be unworkable.